Defining Fc-mediated Functions in People Living with HIV during Respiratory Viral Infection and Vaccination - Motsoeneng, Boitumelo Madika (University of the Witwatersrand, Johannesburg, 2024)
There are approximately 39 million people living with human immunodeficiency virus (HIV) (PLWH) worldwide. Furthering our understanding of humoral immune responses to respiratory viral infection and vaccination in PLWH is essential for reducing the burden of these diseases, in high HIV prevalence settings, and informing vaccine implementation in this population. Influenza virus hemagglutinin (HA) stalk-specific antibodies have been associated with protection and shown to mediate Fc-mediated functions. This thesis describes HA stalk-specific antibody- dependent cellular phagocytosis (ADCP), cellular cytotoxicity (ADCC) and complement deposition (ADCD) between PLWH and people without HIV (PWOH) following immunization with a seasonal trivalent inactivated influenza vaccine (TIV). Irrespective of HIV status, ADCD was boosted while ADCC was not. ADCP was only enhanced in PWOH. The coordination of these functions differed by HIV status. Additionally, differences in the regulation of these HA stalk Fc responses by HIV infection was reported. Furthermore, ADCC was not associated with protection in this study. Pre- existing ADCP reduced the risk of influenza virus infection while TIV-induced ADCD provided protection against influenza-illness. Overall, PLWH have unique responses to TIV and HA stalk- specific ADCD correlated with protection following TIV. For SARS-CoV-2, antiretroviral treatment (ART)-naïve PLWH had reduced humoral responses to respiratory infection. The infecting variants D614G and Beta differentially triggered ADCC, ADCD and antibody-dependent cellular trogocytosis (ADCT). Regarding the kinetics, PLWH infected with D614G had delayed neutralization and ADCP while Beta infection delayed ADCT, regardless of HIV status. PLWH showed improved coordination between immune responses following respiratory infection. ChAdOx-1 nCoV-19 vaccination differed from infection in that PLWH had delayed IgG binding while neutralization and ADCP were not delayed, and ADCC was substantially enhanced than in PWOH. In conclusion, despite the delayed and differential kinetics, PLWH on ART developed equivalent responses to PWOH, supporting the rapid rollout of ART and SARS-CoV-2 vaccines to PLWH. This thesis highlights the need to include high-risk groups with different responses in future vaccination trials and also supports the assessment of novel correlates of protection for future vaccines. Overall, this thesis provided insights into the mechanisms required for protection against severe respiratory diseases and improved our understanding of vaccine-induced immunity in PLWH
A thesis submitted in fulfillment of the requirements for the degree of Doctor of Philosophy to the Faculty of Health Sciences, School of Pathology, University of the Witwatersrand, Johannesburg, 2024
Keywords: Fc-mediated functions; People living with HIV (PLWH); Influenza vaccination; Antibodies; Protection; Humoral response kinetics; UCTD; SDG-3: Good health and well-being